Pembangunan model konseptual e- CAV sebagai penambahbaikan kaedah bimbingan School Improvement Partners+ (SIPartners+) dalam kalangan kepimpinan sekolah di negeri Pahang, Terengganu dan Kelantan - Mohd Azuri, Shaari (2020)
Starting from 2013 each School Leadership (SL) in Malaysia will have school partners for school improvement and name it as School Improvement Partners (SIPartners +) which is described as a critical friend and his role is to support and challenge SL. This is based on the National Education Blueprint (2013-2025), and it’s contained in the sixth shift outlined in the blueprint that must be reached in the next wave of 2013-2015. This study was undertaken because there is a variety of different perceptions of the SL in between SIPartners + in terms of guidance, skills, experience, support and challenge provided by SIPartners +. This is a study involving three states on the East Coast of Peninsular Malaysia, Pahang, Kelantan and Terengganu and were evaluated on the basis of the needs of the country from the perspective of direct recipients of KS and a total of 360 respondents participated in the study. This study was carried out to achieve six objectives of the study, which identified the perception KS on the effectiveness of counseling SIPartners + guide them, identify the level of acceptance KS to SIPartners + guide them, determining the effectiveness of counseling SIPartners + in improving the Starting from 2013 each School Leadership (SL) in Malaysia will have school partners for school improvement and name it as School Improvement Partners (SIPartners +) which is described as a critical friend and his role is to support and challenge SL. This is based on the National Education Blueprint (2013-2025), and it’s contained in the sixth shift outlined in the blueprint that must be reached in the next wave of 2013-2015. This study was undertaken because there is a variety of different perceptions of the SL in between SIPartners + in terms of guidance, skills, experience, support and challenge provided by SIPartners +. This is a study involving three states on the East Coast of Peninsular Malaysia, Pahang, Kelantan and Terengganu and were evaluated on the basis of the needs of the country from the perspective of direct recipients of KS and a total of 360 respondents participated in the study. This study was carried out to achieve six objectives of the study, which identified the perception KS on the effectiveness of counseling SIPartners + guide them, identify the level of acceptance KS to SIPartners + guide them, determining the effectiveness of counseling SIPartners + in improving the quality of KS, determining factor effectiveness of the guidance provided by SIPartners + in improve the quality of KS, measure whether there is a significant relationship between the effectiveness of the guidance SIPartners + against the backdrop of KS in implementing the school management, and developing and propose a conceptual model improvement coaching role SIPartners + in helping to improve the skills of SL towards transformational leadership and high impact. This study is based on quantitative methods and findings data that were analyzed using SPSS IBM version 24.0. This study has used CIPP model. The theoretical model approach consisting of Context, Input, Process, Product approach by Stufflebeam. Overall, the findings of this research study were at high level achievement and the analysis shows a positive response among all of the principals and objectives of the study showed positive results and support to the implementation and relevance of the practice guidance by SIPartners + to SL. The implications of this study are expected in the MOE or District Education Office (DEO) can consider the use of e- CAV who have successfully built and proposed in this study to design and implement a model of mentoring new or improved so SL can improve the professional quality of school leadership agenda in order to transform schools to become more effective and in line with the current policy contained in the policy of MOE.